IMPLEMENTATION OF RISK-BASED RECEIVABLES LOSS PROVISION AT ABC SYARIAH BANK - Dinar Ary Kartikasari; Driana Leniwati; Nazaruddin Malik (RADJA PUBLIKA, 2025)
This study aims to analyze the influence of Non-Performing Financing (NPF) and risk-based Allowance for Impairment Losses (CKPN) on Contribution Margin in the commercial segment of Bank Syariah ABC. The research employs a mixed methods approach with a Sequential Explanatory design, where quantitative analysis is conducted using multiple linear regression and complemented with qualitative analysis through in-depth interviews. The quantitative results show that both NPF and CKPN have a positive and significant effect on the Contribution Margin. A measured increase in CKPN, calculated based on the Expected Credit Loss (ECL) model, strengthens the long-term financial stability of the bank. Meanwhile, effective management of NPF through restructuring and collateral-based financing mitigates its potential negative impact on the margin. The qualitative findings support the statistical results, revealing that the quality and timeliness of customers' financial reporting are critical factors in the accuracy of ECL estimation. Delays in reporting and the lack of adequate accounting systems among commercial clients present challenges in determining optimal CKPN levels. Therefore, the role of risk management, technological support, and strengthened reporting governance are strategic aspects to enhance risk control in the commercial financing segment. This research contributes to the development of a risk-based provisioning system that not only complies with PSAK 71 and OJK regulations but also supports the sustainability of contribution margin in Islamic financing practices